2019
DOI: 10.3390/su11030615
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment Using Fuzzy TOPSIS and PRAT for Sustainable Engineering Projects

Abstract: In this study, we propose a safety risk assessment process using the fuzzy extension of the technique for order of preference by similarity to ideal solution (TOPSIS) for assigning priorities to risks in worksites, in order to promote the health, safety and well-being of workers, issues that are embedded within the concept of sustainability, specifically belonging to the social sphere of sustainability. The multicriteria method works in cooperation with a simple quantitative risk analysis and assessment proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…However, visual qualification labels can be used and affixed to electrical equipment to strengthen qualification controls and audit electrical equipment (i.e., judging if electrical equipment is qualified for operations on the construction site) and ultimately enhance the overall electrical operation safety of the construction site. Occupational hazard statistics from the United States and European Union countries have clearly indicated that a healthy and safe work environment is critical for enhancing labor productivity and enterprise competitiveness [25]. For construction units, routine equipment inspection and maintenance can significantly enhance safety and reduce costs from occupational hazards [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, visual qualification labels can be used and affixed to electrical equipment to strengthen qualification controls and audit electrical equipment (i.e., judging if electrical equipment is qualified for operations on the construction site) and ultimately enhance the overall electrical operation safety of the construction site. Occupational hazard statistics from the United States and European Union countries have clearly indicated that a healthy and safe work environment is critical for enhancing labor productivity and enterprise competitiveness [25]. For construction units, routine equipment inspection and maintenance can significantly enhance safety and reduce costs from occupational hazards [5].…”
Section: Discussionmentioning
confidence: 99%
“…TOPSIS method finds out the shortest distance of the alternative to the ideal solution and ranks it as the best one (Zavadskas et al, 2016). TOPSIS method is widely used in many fields: assessing EURO 2020 strategy (Ture et al, 2019), evaluating strategies for sustainable energy planning (Solangi et al, 2019), risk assessment for sustainable engineering projects (Koulinas et al, 2019), product design concept evaluation (Tiwari et al, 2019), measuring the maturity of the carbon market in China (Liu et al, 2019b), measurement of regional green economy sustainable development ability (Wang et al, 2019).…”
Section: Mcdm Methods In the Assessment Of Ecoinnovation In The Context Of Circular Economymentioning
confidence: 99%
“…MCDM is known as a method to solve the multiple conflicting criteria in selecting the best ranking and providing an option from the feasible solution alternatives [24]. Some of the alternative cases are connected to MCDM criteria weight problem using a decision matrix as Koulinas's research [28]. In MCDM of classical methods, the rankings of variable and the weights of the criteria are known precisely in the papers [15,19,25,27,29].…”
Section: Multiple Criteria Decision-making (Mcdm)mentioning
confidence: 99%